Impact of 17β Estradiol on Sex Ratio and Reproductive Output of The Catfish Heteropneustes fossilis (Bloch.) - V. Ramanathan, M. Velu* and (Journal of Experimental Sciences, 2011)
Many of synthetic chemicals (xeno - estrogens) have been shown to interact as agonists with the estrogen receptor (ER) and to elicit biological responses similar to those of the natural steroid hormones. Estradiol is the main compound responsible for the estrogenic activity in sewage treatment works effluents and given these concentrations, those found in surface waters, and its estrogenic potency, E2 is now considered as an important contaminant of the aquatic environment. Despite this, little is known about the biological effects of exposure to low concentrations of E2, or the sensitivity of different fish life stages to the disruptive effects of E2. To assess the effects on reproduction of exposure of adult catfish to E2, the fish used were 7-month-old. For each treatment group (5, 25, 100 ng E2/l, solvent control and dilution water control) a single tank containing 10 females (length 39.4mm ± 0.25; weight 56 mg ± 11.63) and 20 males (length 35.8 ± 0.23; weight 38 mg ± 7.7) was set up. The exposure tanks were 40 cm long × 20 cm wide × 25 cm high. Reproductive performance in each treatment group was followed for a 3-week-period prior to exposure to E2 and during a 3-week-period during the exposure to E2. Fish were maintained in the same tanks for the spawning assessments prior to and during E2 exposures and therefore, the pre-exposure spawning events were assigned as the controls for the subsequent E2 exposures for each regime. Fecundity and fertilization success in the F0 generation and hatchability in the F1 generation were assessed daily. Gonadal sections in males were examined for the presence of oocytes in the testis, alterations in testicular structure and the presence of Sertoli cells. In female gonads, the stages of oocyte development were also examined and for this purpose 50 follicles per couple and per female were identified and counted.Statistical analyses were done using One-way analysis of variance (ANOVA) followed by Duncan’s multiple range test was used. In the present study, the effects of exposure to E2 during various life stages on vitellogenin induction, gonadal histology and reproductive output in the catfish Heteropneustes fossilis was undertaken. This work demonstrated that exposure to E2 resulted in vitellogenin induction whatever the life stage exposed but these effects were reversible after a depuration period. Exposure to 100 ng E2/l from fertilization to 21 dpf also caused a disruption of the sexual differentiation as assessed by the skewed sex ratio in the subsequent adult population. Exposure during early life stages also resulted in an altered pattern of egg production in the subsequent adults. Exposure of catfish as adult to E2 led to a modification of the secondary sexual characteristics at 100 ng E2/l and a decrease of egg production. Taken together, these data showed the nature and level of the effects of E2 are dependent on the timing of the exposure with some effects being permanent (gonad differentiation) and others reversible (Vtg induction). This study demonstrated that early life stages of the fish are sensitive to low concentrations of E2 leading to partial feminization of the population and to vitellogenin induction and highlight the effects on vulnerable developmental stages. Moreover these data raise further concerns about the effects of steroid estrogens in the environment on fish reproductive health.